Islamic civilization: its significance in al-Faruqi’s Islamization of Knowledge - Wan Sabri, W.Y.; Zuriati, M.R.; Tasnim, A.R.; Ahmad, N.A. (Universiti Kebangsaan Malaysia, 2015)
This paper discusses the significance attempt of al-Faruqi in making Islamic civilization a mandatory course in his Islamization of Knowledge project. In any attempt of Islamization of Knowledge, the students of Islamization should be comprehensively mastered Islamic Civilization. Al-Faruqi systematically developed four required components in civilizational study that were critical for Islamization project, i.e., to give the Muslim student knowledge of the first principles of Islam as essence of Islamic civilization in the first year; the historical achievements of Islamic civilization in the second year; how Islamic civilization compares and contrasts with other civilizations in essence and manifestation, in the third year, and; how Islamic civilization is the only viable option in dealing with the fundamental problems of Muslims and non-Muslims in the contemporary world, in the fourth year. The significance ideal projected by this comprehensive stages as characterized by al-Faruqi were crucial for student to understand the secular worldview that bring the collapse of civilization in the past and not to repeat this catastrophic consequence in contemporary civilization of the Ummah.